Synthesis of Ag2CrO4/SnO2 n–n type heterojunction as a visible light photocatalyst for degradation of rhodamine B - Wu, Xiang-Feng; Zhang, Chen-Xu; Wang, Yu-Duan; Su, Jun-Zhang; Zhang, Jia-Rui; Feng, Yan-Mei; Zhang, Mi; Tong, Xin; Zhang, Wei-Guang; Sun, Xiu-Guo (Journal of materials science. Materials in electronics, 2018)
The Ag 2 CrO 4 /SnO 2 n–n type heterojunction has been fabricated by coupling Ag 2 CrO 4 particles with SnO 2 nanorods via an in situ synthetic method. The photocatalytic degradation mechanism of the as-prepared heterojunction has also been discussed. Characterization results revealed that the as-fabricated Ag 2 CrO 4 /SnO 2 composites could reinforce the photo-degradation competencies for rhodamine B dilute solution compared to pure Ag 2 CrO 4 and SnO 2 samples. As the increase in the molar ratios of Ag 2 CrO 4 –SnO 2 , the photocatalytic degradation efficiency appeared to the tendency of first increasing and then decreasing. When it was 4:10, in 90 min, the as-obtained samples possessed the vintage photocatalytic degradation efficiency of 95.8% among of pure SnO 2 , Ag 2 CrO 4 and the as-prepared composites with various molar ratios, respectively. Furthermore, the Ag 2 CrO 4 and SnO 2 were connected via chemical bonds to form the homogenous heterojunction. It could boost the separation and transfer of the photogenerated holes and electrons. In addition, the holes, hydroxyl and superoxide radicals played a major role during the photodegradation process.